Root Restriction for Growth Control and Precocity in Starfruit (A Verrhoa Carambola L.) - Meon, Zainudin (2001)
Starfruit (Averrhoa carambola) is an important fruit grown commercially in Malaysia. High rainfall and plentiful sunshine of the humid tropic usually promotes abundant shoot growth. Tree height increment is also tremendously fast. These conditions could lead to increase vegetative growth. Innovative technique is therefore needed to control vegetative vigour. Root restriction offers an effective and safe method of reducing tree size and canopy development. The main objective of this research is to study the response of starfruit to root restriction treatments under in the glasshouse and field condition. Root restriction studies have previously been conducted mainly in starfruit, they were preceded by preliminary studies on apple (Malus domestica) and pear (Pyurus communis) in the United Kingdom. Preliminary studies in apple grown in different container shapes and volumes showed that root and shoot growth responded to both container dimensions and their interactions. Large volumes (1 2 litre) with high pot depths enhanced root growth, thereby increasing shoot growth. However, effects of root growth restriction were observed when container shape or volume was reduced resulting in decreased root and shoot growth, and nutrient levels. Root : shoot ratio remained consistent irrespective of changes in container volume or shape. Studies on pear trees (Py rus comm unis) subjected to different shapes and volumes Df porous root restrictive membrane suggested that reduction in soil volume to 9 1 litres resulted in 35 and 38% reduction in girth increment and shoot length, respectively. Fruitset and average weight per fruit were unaffected, but leaf P concentration was reduced during the first year of plailting. Similar treatments tested on starfruit (Av errho a c aram bo la) grown in different container shapes and volumes indicated that gmwth responded mostly to container volumes. Root and shoot growth reduced with decrease in container volume. Detailed root studies using root observation chambers showed that reduction in chamber volume decreased root branching and root elongation but root length density (RLD) increased although coarse root length and root tip density did not change. Root surface area (RSA) was also reduced when root chamber volume decreased. It was concluded that the reduction in shoot growth was the result of reduced root growth and development.